Chitosan-Based Structural Color Films for Humidity Sensing with Antiviral Effect - Darya Burak; Dong-Chan Seo; Hong-Eun An; Sohee Jeong; Seung Eun Lee; So-Hye Cho (Nanomaterials, 2024)
This scientific investigation emphasizes the essential integration of nature’s influence in crafting multifunctional surfaces with bio-inspired designs for enhanced functionality and environmental advantages. The study introduces an innovative approach, merging color decoration, humidity sensing, and antiviral properties into a unified surface using chitosan, an organo-biological polymer, to create cost-effective multilayered films through sol-gel deposition and UV photoinduced deposition of metal nanoparticles. The resulting chitosan films showcase diverse structural colors and demonstrate significant antiviral efficiency, with a 50% and 85% virus inhibition rate within a rapid 20 min reaction, validated through fluorescence cell expression and real-time qPCR (polymerase chain reaction) assays. Silver-deposited chitosan films further enhance antiviral activity, achieving remarkable 91% and 95% inhibition in independent assays. These films exhibit humidity-responsive color modifications across a 25–90% relative humidity range, enabling real-time monitoring validated through simulation studies. The proposed three-in-one functional surface can have versatile applications in surface decoration, medicine, air conditioning, and the food industry. It can serve as a real-time humidity sensor for indoor and outdoor surfaces, find use in biomedical devices for continuous humidity monitoring, and offer antiviral protection for frequently handled devices and tools. The customizable colors enhance visual appeal, making it a comprehensive solution for diverse applications.